3,3’-Diindolylmethane Enhances Paclitaxel Sensitivity by Suppressing DNMT1-Mediated KLF4 Methylation in Breast Cancer - Xiang, Fenfen; Zhu, Zhaowei; Zhang, Mengzhe; Wang, Jie; Chen, Zixi; Li, Xiaoxiao; Zhang, Tao; Gu, Qing; Wu, Rong; Kang, Xiangdong (Frontiers in Oncology, 2021)
Paclitaxel (PTX) is a first-line chemotherapeutic drug for the treatment of breast cancer, but drug resistance seriously limits its clinical use. The aim of the present work was to explore the effect of 3,3'-diindolylmethane (DIM) on PTX sensitivity and its possible mechanism in breast cancer. The expression of Krüppel-like factor 4 (KLF4) and DNA-methyltransferase 1 (DNMT1) in breast cancer tissues were assessed by immunohistochemistry and Western blotting. The methylation of KLF4 was evaluated by the MassARRAY platform. The lentivirus carrying KLF4 and DNMT1 gene or shRNA targeting DNMT1 were used to overexpress KLF4 or knockdown DNMT1 in MCF-7 and T47D breast cancer cells and the role of KLF4 and DNMT1 in regulation of PTX sensitivity was investigated. The effect of PTX on inhibiting the proliferation of MCF-7 and T47D cells was measured by CCK-8 assay. Flow cytometry was used to examine cell apoptosis. The expression of mRNA and protein was evaluated by qRT-PCR and Western blotting analysis, respectively. Our data showed that the expression of DNMT1 was increased, and the methylation level of CpG sites (−148 bp) in the KLF4 promoter was increased while the KLF4 expression was significantly decreased in breast cancer tissues. Overexpression of KLF4 increased the sensitivity of MCF-7 and T47D cells to PTX. DNMT1 increased the methylation of the KLF4 promoter and decrease the expression of KLF4. Knockdown of DNMT1 increased the sensitivity of MCF-7 and T47D cells to PTX. DIM enhanced the PTX sensitivity of MCF-7 and T47D cells, decreased the expression of DNMT1 and the methylation level of KLF4 promoter, thus increasing the level of KLF4. Furthermore, overexpression of DNMT1 attenuated the effect of DIM on the regulation of PTX sensitivity. Collectively, our data indicated that DNMT1-mediated hypermethylation of KLF4 promoter leads to downregulation of KLF4 in breast cancer. The level of KLF4 is correlated with the sensitivity of MCF-7 and T47D cells to PTX. DIM could enhance the antitumor efficacy of PTX on MCF-7 and T47D cells by regulating DNMT1 and KLF4.